2013
DOI: 10.3390/md11093224
|View full text |Cite
|
Sign up to set email alerts
|

Epigonal Conditioned Media from Bonnethead Shark, Sphyrna tiburo, Induces Apoptosis in a T-Cell Leukemia Cell Line, Jurkat E6-1

Abstract: Representatives of Subclass Elasmobranchii are cartilaginous fish whose members include sharks, skates, and rays. Because of their unique phylogenetic position of being the most primitive group of vertebrates to possess all the components necessary for an adaptive immune system, the immune regulatory compounds they possess may represent the earliest evolutionary forms of novel compounds with the potential for innovative therapeutic applications. Conditioned medium, generated from short term culture of cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Recent genome studies of largely bottom-dwelling chondrichthyans (elephant shark, brownbanded bamboo shark, and cloudy catshark) have reported a distinct paucity of odorant receptor genes (4,6), raising the question of whether this would also be the case in a pelagic apex predator, which migrates great distances, such as the white shark. There are anecdotal reports that elasmobranchs have a low incidence of documented cancers (12), but these observations remain unconfirmed given the absence of systematic surveys to investigate the question (13). There are also empirical studies reporting on a medium generated from the culture of cells from the epigonal organ of bonnethead sharks (Sphyrna tiburo), exhibiting cytotoxic activity against human tumor cell lines, via the induction of apoptosis in the target cells (12,14).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome studies of largely bottom-dwelling chondrichthyans (elephant shark, brownbanded bamboo shark, and cloudy catshark) have reported a distinct paucity of odorant receptor genes (4,6), raising the question of whether this would also be the case in a pelagic apex predator, which migrates great distances, such as the white shark. There are anecdotal reports that elasmobranchs have a low incidence of documented cancers (12), but these observations remain unconfirmed given the absence of systematic surveys to investigate the question (13). There are also empirical studies reporting on a medium generated from the culture of cells from the epigonal organ of bonnethead sharks (Sphyrna tiburo), exhibiting cytotoxic activity against human tumor cell lines, via the induction of apoptosis in the target cells (12,14).…”
Section: Significancementioning
confidence: 99%
“…There are anecdotal reports that elasmobranchs have a low incidence of documented cancers (12), but these observations remain unconfirmed given the absence of systematic surveys to investigate the question (13). There are also empirical studies reporting on a medium generated from the culture of cells from the epigonal organ of bonnethead sharks (Sphyrna tiburo), exhibiting cytotoxic activity against human tumor cell lines, via the induction of apoptosis in the target cells (12,14).…”
Section: Significancementioning
confidence: 99%
“…Recent studies have demonstrated that in 72-96 h culture of bonnethead shark, Sphyrna tiburo, epigonal cells secrete compounds into the surrounding culture medium, termed 'epigonal conditioned medium', that inhibit the growth of several tumor cell lines [86]. Specifically, compounds in this epigonal cell conditioned medium have been shown to induce apoptosis in a T-cell leukemia cell line (Jurkat) through binding to the TRAIL receptor and activating the mitochondrial caspase-mediated pathway [87]. Moreover, the compounds in this conditioned medium preferentially target transformed cells as opposed to normal cells [87].…”
Section: Elasmobranch Immune Cell-derived Compoundsmentioning
confidence: 99%
“…Specifically, compounds in this epigonal cell conditioned medium have been shown to induce apoptosis in a T-cell leukemia cell line (Jurkat) through binding to the TRAIL receptor and activating the mitochondrial caspase-mediated pathway [87]. Moreover, the compounds in this conditioned medium preferentially target transformed cells as opposed to normal cells [87]. Efforts are underway to identify bioactive components for further evaluation as potential therapeutic agents.…”
Section: Elasmobranch Immune Cell-derived Compoundsmentioning
confidence: 99%
“…Penipacids A and E are cytotoxic to human colon cancer RKO cells [ 21 ]. Walsh and colleagues from the USA describe caspase-dependent and mitochondrial pathway-related apoptosis in leukemia cells in response to treatment with epigonal conditioned medium from the bonnethead shark, Sphyrna tiburo [ 22 ]. Su and colleagues from Taiwan and Egypt investigate the mechanism underlying the cytotoxic action of (1′ R ,5′ S ,6′ S )-2-(3′,5′-dibromo-1′,6′-dihydroxy-4′-oxocyclohex-2′-enyl) acetonitrile , previously isolated from the sponge Pseudoceratina sp., in leukemia cells.…”
Section: Research Articlesmentioning
confidence: 99%